The 80/20 principle : the secret to achieving more with less - Koch, Richard (New York : Currency, 2017)
The 80/20 Principle can and should be used by every intelligent person in their daily life, by every organization, and by every social grouping and form of society. It can help individuals and groups achieve much more, with much less effort. The 80/20 Principle can raise personal effectiveness and happiness. It can multiply the profitability of corporations and the effectiveness of any organization. It even holds the key to raising the quality and quantity of public services while cutting their cost. This book, the first ever on the 80/20 Principle,2 is written from a burning conviction, validated in personal and business experience, that this principle is one of the best ways of dealing with and transcending the pressures of modern life.
Includes bibliographical references and index.
ne 19/08/2022
Loans
Keywords: Time management; Labour productivity--Psychological aspects; Industrial efficiency--Psychological aspects; Conduct of life